Recent Advances in the Nanocatalyst-Assisted NaBH4 Reduction of Nitroaromatics in Water - Zhang, Kaiqiang; Suh, Jun Min; Choi, Ji-Won; Jang, Ho Won; Shokouhimehr, Mohammadreza; Varma, Rajender S. (AMER CHEMICAL SOC, 2019)
In view of the increasing applications of nanocatalysis in chemical transformations, this article illustrates recent advances on the use of nanocatalysts for an important reduction reaction, the hydrogenation of nitroaromatics to significant aminoaromatics with aqueous NaBH4 solution; the utility of mono- and multimetal nanocatalysts with special emphasis on heterogeneous nanocatalysts is included. A progressive trend on the applicability of nanocatalysts is also incorporated with large-scale application and their sustainable recyclization and reuse utilizing supported and magnetic nanocatalysts; representative methods for the synthesis of such reusable nanocatalysts are featured.
Keywords: ENHANCED CATALYTIC-ACTIVITY; CORE-SHELL NANOPARTICLES; AROMATIC NITRO-COMPOUNDS; RECYCLABLE HETEROGENEOUS CATALYST; ONE-STEP SYNTHESIS; SILVER NANOPARTICLES; GOLD NANOPARTICLES; HIGHLY EFFICIENT; NANOCOMPOSITE CATALYSTS; PALLADIUM NANOPARTICLES